Effect of Sucrose and Glycerol Based Cryoprotective Media on Kinetic Characteristics of Saanen Goat Spermatozoa - Bogdaniuk , Anastasiia; Garkavii , Volodymyr; Tsvyk , Vasyl (Problems of Cryobiology and Cryomedicine, 2020)
Probl Cryobiol Cryomed 2020; 30(3): 283